2018
DOI: 10.1038/s41598-018-20667-9
|View full text |Cite
|
Sign up to set email alerts
|

Mud Banks along the southwest coast of India are not too muddy for plankton

Abstract: Considering Alappuzha Mud Bank in the southern Kerala coast as a typical case of biologically productive Mud Banks that form along the southwest coast of India during the Southwest Monsoon (June - September), the present study addresses several pertinent missing links between the physical environment in Mud Banks and their influence on plankton stock. This study showed that very strong coastal upwelling prevails in the entire study domain during the Southwest Monsoon, which manifests itself in the form of sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Upwelling along the southwest coast of India enriches the coastal waters with a high concentration of essential nutrients facilitating an increase in phytoplankton biomass (Bhattathiri et al 1996;Qasim 1982;Madhupratap et al 1990;Jyothibabu et al 2008;Karnan et al 2017a;Karnan et al 2020). This enhancement in autotrophs biomass during the Southwest Monsoon is well imprinted in satellite imageries of chlorophyll-a as well, but information about the dominant phytoplankton behind such a biomass increase is limited (Jyothibabu et al 2010(Jyothibabu et al , 2018aKarnan et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Upwelling along the southwest coast of India enriches the coastal waters with a high concentration of essential nutrients facilitating an increase in phytoplankton biomass (Bhattathiri et al 1996;Qasim 1982;Madhupratap et al 1990;Jyothibabu et al 2008;Karnan et al 2017a;Karnan et al 2020). This enhancement in autotrophs biomass during the Southwest Monsoon is well imprinted in satellite imageries of chlorophyll-a as well, but information about the dominant phytoplankton behind such a biomass increase is limited (Jyothibabu et al 2010(Jyothibabu et al , 2018aKarnan et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In most of the studies on the entire west coast, the Southwest Monsoon period is the most productive time because of the proportionate availability and replenishment of nutrients [27,21,58,59]. Also, except at points close to the sea bottom, the turbidity level in the Alappuzha Mudbank was below the critical level to inhibit the plankton stock [60]. The research output in sediment dynamics, biogeochemical processes like sulfate reduction/nitrogen cycle and metal enrichment/ contamination in the coastal sediments in three distinct depositional milieus like estuaries, mangroves, and mudbanks in India were reviewed by and found these regimes as highly productive [61].…”
Section: Biogeochemical Processes In Mudbanksmentioning
confidence: 99%
“…Based on the associated benthic foraminiferan fauna, which is characterized by mesophotic taxa (Brigulio and Rögl, 2018; Rögl and Brigulio, 2018), it has been recently suggested that the seagrass fauna was transported from seagrass beds, which grew in ~20–30 m water depth, down to 60–70 m water depth (Brigulio et al, 2018). This paleobathymetric reconstruction, however, has to be taken with caution because it does not consider the attenuation of light in seagrass canopies (e.g., Hedley et al, 2014) and turbid coastal waters along southern Kerala (Jyothibabu et al, 2018).
Figure 1.( 1 ) Locality maps and stratigraphic summary.
…”
Section: Geological Settingmentioning
confidence: 99%